Answer:
y = -15
x = -10
Step-by-step explanation:
1/4x - 1/2 = 5 (1)
3x + 2/3y = -40 (2)
Multiply (1) by 4
1/4x - 1/2 = 5
1/4x * 4 - 1/2y * 4 = 5 * 4
4/4x - 4/2y = 20
x - 2y = 20 (3)
Multiply (2) by 3
3x + 2/3y = -40 (2)
3x * 3 + 2/3y * 3 = -40 * 3
9x + 6/3y = -120
9x + 2y = -120 (4)
x - 2y = 20 (3)
9x + 2y = -120 (4)
Using elimination method, Add (3) and (4)
9x + x = -120 + 20
10x = -100
x = -100/10
x = -10
Substitute x = -10 into (3)
x - 2y = 20 (3)
-10 - 2y = 20
-2y = 20 + 10
-2y = 30
y = 30/-2
y = -15
y = -15
x = -10